Análise do conflito entre pescadores artesanais e funcionários do Parque Nacional da Lagoa do Peixe, uma unidade de conservação de proteção integral - Doebber, Camila (Universidade do Vale do Rio dos Sinos, 2017)
The Lagoa do Peixe National Park, created in 1986 on the middle coast of Rio Grande do Sul, is a conservation unit (CU) of integral protection, where the use of natural resources is not allowed in its territory, generating conflicts between PARNA’s administration and the traditional communities that lived in that area even before the CU creation. The objective of this work was to describe the perception and knowledge of fishermen and PARNAs ICMBio employees about the conflict, searching for suitable solutions. To do so, semi-structured interviews were conducted with 96 fishermen (of the 127 registered) and 11 ICMBio employees, using questionnaires containing 63 questions in the case of fishermen and 33 in the case of employees (questions being open and closed, arranged in Likert scale). Among the fishermen, 60 believed that fishing at PARNA may be prohibited in the near future and most of them (68,8%) showed some degree of concern about their fishing activity in the PARNA verifying the desire to remain in the fishing activity. In case the fishing was forbidden, 91% of fishermen would like to receive a monetary compensation. PARNA employees also cited financial aid as a form of compensation, besides training courses for other activities (e. g. tourism) to mitigate the conflict. As alternative activities for the fishermen the employees cited agriculture, fish farming, livestock, forestry and handcraft activities. Besides that, fishermen and employees see some touristic potential for PARNA as an alternative activity in relation to fishing, where there is the possibility for the fishermen to work in the tourism sector inside PARNA, in activities as guides, maintenance and direct assistance to visitors. However, the perception of the fishermen is that even though their representatives exist on the Advisory Council of PARNA, there is still difficulty in their internal dialogue, as well as the small knowledge about the decisions coming from meeting of the Advisory Council. On the other hand, there is the fishermen perception that the dialogue between the management team and fishermen has been improving over the years, and that fisherman have some knowledge of local fisheries legislation. The obtained answers showed that most of fishermen and employees see an economical solution for the case of the future fishing prohibition at PARNA, which is feasible in the terms of law. The precondition is the implementation of a social and economic program for the absorption of their labor in a socially and economically dignified conditions, as tourism for example. However, the desire for fishing continuity by the fishermen in PARNA suggests alternative solutions that allow their stay in the place, as the elaboration of a Commitment Term, according to Normative Instruction nº 26/2012, or the re-categorization of the conservation unit, making part of Lagoa do Peixe a conservation unit for sustainable use, such as an Extractive Reserve.
Keywords: Pesca artesanal; Áreas protegidas; Manejo participativo; Uso público; Artisanal fishing; Protected areas; Participatory management; Public use; ACCNPQ::Ciências Biológicas::Biologia Geral